Descrição do serviço de gestão da condição da saúde voltado a crianças recém-diagnosticadas com doença falciforme - Elaine F. DIAS (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2021)
Objective: To assess the results of the health condition management service provided for children with sickle cell disease (SCD). Methods: a cross-sectional study of the health condition management service offered to newly diagnosed children with SCD treated between January 2016 and December 2019 at the Blood Center in Belo Horizonte, Brazil. The service was provided by a clinical pharmacist and an academic from the pharmacy course, with data from the initial consultation (start of drug use) performed in a pharmacist’s office and telephone contact carried out eight days later. All children seen at the service were evaluated, and their demographic characteristics, compliance with the beginning of the use of prophylactic drugs for sickle cell disease (phenoxymethylpenicillin and folic acid) according to the protocol of the Ministry of Health (within 90 days after birth), and documented reason in case of non-compliance. The doubts regarding the medications and the standardized interventions of the service to the children´s guardians were also described. The difference in the distribution of variables in the adequacy and non-adequacy group to the MS protocol was assessed using Pearson’s chi-square test (categorical) and Mann-Whitney (numerical). Results: In the SCD condition management service, all children together with their guardians (N = 298) had their first consultation with the pharmacist (initial dispensation day), however, only 185 (62.1%) participated in the pharmaceutical service by telephone (eight days after the initial dispensing). Approximately 88.3% of children started using drugs for sickle cell disease according to the protocol of the Ministry of Health; the most frequent reason for non-compliance was the late diagnosis in the complementary health system (22.9%). The guardians pointed out 63 doubts about the medications, highlighting their non-acceptance by the child (28.6%), and for all doubts standard pharmaceutical guidelines were provided in the service. Conclusion: It was identified that the health condition management service provided is relevant, since most of those responsible for the children with SCD had doubts about their medication after the administration of medications began. The pharmacist contributes positively to the pharmacotherapeutic management of SCD, promoting empowerment about the correct use of medicines.